Perspektif terkait penerapan nilai pancasila pada mahasiswa Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Surakarta - Kristanti, Anisa; Setiaji, Calista Amalia; Antika, Lianwy Rindi; Nur, Silma Dahlia; Solekhan, Annisa Septiyana (Journal of Smart Education and Learning, 2024)
This study aims to determine the perspective of applying Pancasila values to Elementary School Teacher Education Students of the Muhammadiyah University of Surakarta. In the current era of open life, people's lives are colored by life patterns that are not always in line with the values contained in Pancasila. To counteract the negative impacts of the globalization era, awareness is needed to apply Pancasila values in every aspect of life. This study uses a qualitative method with a phenomenological approach based on subjective or phenomenological experiences experienced by individuals. The study results show that almost all students understand what Pancasila is. Then, in one of the questions asked regarding students' understanding of Pancasila and its contents, several sources have different opinions. This condition happens due to differences in perspective or the portion of one's assessment of others. It also shows that elementary school teacher education students at Muhammadiyah University of Surakarta know Pancasila. However, not all of them understand and properly apply the values of Pancasila in their daily lives.